ECONOMICS, CHRISTIANITY AND THE CRISIS: KUYPER’S HERITAGE AND RELEVANCE TODAY - Goudzwaard, Bob (Philosophia reformata, 2013)
One hundred twenty years ago, to be more precise on 9 November 1891, Abraham Kuyper opened the first social congress in the Netherlands He did so with an outstanding lecture on the relationship between the so-called social question and the christian religion. He began the lecture however with a remarkable complaint (Kuyper 1991, 23): One of the pitiful fruits of state monopoly, which continues to increase in this country’s universities, is that we have not yet even produced academic specialists. None of us at this Congress stands out as an expert in economics. If I look around me now, that seems to be a little bit different from what I see today. But I doubt whether that in itself is a guarantee of greater wisdom amongst us. Let us not be too hasty. Let us wait and see.